The Difficulties Faced by Teachers in Implementing the Smart Schools Project in Iraq - Ahmed Al-Bayati, Tabarak Shihab (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This research explores the obstacles teachers encounter in executing the smart schools initiative within the framework of Iraq, where educational facilities and digital preparedness are still at an early stage. Although worldwide trends reveal the growing use of smart technologies in education, Iraq has been hindered by systemic barriers, such as archaic curricula, restricted access to technologies, and an unqualified teaching staff. Data were collected using a validated questionnaire on 122 public school teachers working in Baghdad with a descriptive-analytical methodology. The study divided challenges into five areas: infrastructure, teacher preparedness, administrative support, curricular adaptation and cultural resistance. Data on the overall response rate were analyzed using frequency distributions, and free-text responses were thematically coded. The findings suggest that while the vast majority of teachers support the idea of smart schools in principle, the realization of such facilities/initiatives is still hampered by technological and institutional factors. These recommendations serve as the foundation for specific policy reform, professional development programs, and infrastructure investment that will enable sustainable digital transformation in Iraqi education. The paper ends with practical recommendations for policymakers and educational leaders to align aspiration with reality within smart education.